Estudo da viscoelasticidade de células de câncer renal por microscopia de força atômica - Alencar, Luciana Magalhães Rebêlo (2010)
The mechanical properties of living cells have a crucial role in the accomplishment of their physiological functions. However, our knowledge on this subject is still limited. Is not fully understood how a cell responds structurally and mechanically to an external pressure or as the elasticity of cells is altered in diseased organisms compared to healthy ones. Recently, the biomechanics of cancer cells, in particular the elasticity or stiffness, has been identified as an important factor that is related to function, adhesion, motility, invasion and transformation of the neoplastic cells. Studies in vivo show that cancerous transformations introduce significant changes in the structure and behavior of cells. These differences can cause changes in mechanical properties, often leading to greater cell deformability. Quantifying the change of elasticity using mechanical tests in conjunction with a microscopic examination, can become a powerful method for the diagnosis of cancer, and open new routes for treatments. In this context, Atomic Force Microscopy (AFM) is presented as an ideal tool for cell research due to its high resolution capability for surface nano-manipulation, ability to work in fluids and for being a noninvasive and nondestructive technique. This study investigates the mechanical response of cancer cells (lines A-498 and ACHN), compared to normal cells (RC-124). Using an AFM and its components as a morphological tool of high resolution characterization and characterization of the cells mechanical properties using the AFM probe as a nano-indenter, and from the strength data obtained by the microscope, and appropriate theoretical models to interpret these data to obtain qualitative and quantitative values of the elastic response these cells.